A Study on Financial Risk Management in Pharmaceutical Product Launches at ZIM Laboratories Limited - Dandekar, Maheshwari Dilip; Khaire, Megha (Journal of Neonatal Surgery, 2025)
The pharmaceutical industry faces significant financial risks when launching new products, which can affect overall organizational stability and growth. ZIM Laboratories Limited, a leading player in the pharmaceutical sector, confronts numerous financial challenges during product launches. These include the complexities of market entry, regulatory approvals, and the fluctuating costs of raw materials, all of which contribute to financial uncertainty. This study aims to explore the financial risk management strategies employed by ZIM Laboratories during its pharmaceutical product launches. By analysing internal reports, market trends, and expert interviews, the research identifies key risk factors, including cost overruns, pricing volatility, and supply chain disruptions. It further investigates how risk management techniques such as hedging, insurance, and diversification are applied to mitigate potential financial losses. The findings indicate that while ZIM Laboratories has developed a comprehensive approach to managing financial risks, there remains a need for enhancing predictive analytics and real-time financial monitoring to ensure sustainable profitability. Recommendations are provided for improving the company’s risk assessment models and adopting more adaptive financial strategies in future product launches. This research provides valuable insights for pharmaceutical companies looking to improve their financial risk management frameworks, ensuring more successful product introductions in an increasingly competitive market.